Phenotypic characterization, management and socio-economic impact of Purnathadi buffaloes - S SAJID ALI; S V KURALKAR; M V INGAWALE; S P WAGHMARE; S J MANWAR; R S KATARIA; VIKAS VOHRA (Indian Journal of Animal Sciences, 2019)
A survey was conducted in breeding tract of Purnathadi buffalo with the aim to record its physical, phenotypic and performance traits as well as management practices and the socio economic status were assessed. Purnathadi is a medium sized buffalo, docile in nature with a typical whitish to brown coat colour. Physical and morphometric traits are not only important to identify the group of animals but because of their relationship with performance traits. The studied population of Purnathadi buffalo breed was homogeneous and possessed distinct physical characters those could form the base for identification. Purnathadi buffaloes were preferred by the small and marginal farmers due to low animal cost, high fat% in milk, good reproductive performance and low maintenance cost on feeding and management, however, non-availability of frozen semen and low preference towards maintenance of breeding bull is a major limitation for genetic improvement and conservation of Purnathadi buffaloes. Further, detailed studies for its complete characterization and genetic comparison with other breeds of the region are necessary to register and recognize Purnathadi as separate breed of buffalo, so that breeding plan for conservation and genetic improvement could be designed. This shall increase the interest and confidence of its keepers towards their own germplasm, the Purnathadi buffalo.